2002
DOI: 10.1117/12.469306
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed erbium laser ablation of hard dental tissue: the effects of atomized water spray versus water surface film

Abstract: It has been established that the ability of erbium lasers to ablate hard dental tissue is due primarily to the laserinitiated subsurface expansion ofthe interstitial water trapped within the enamel and that by maintaining a thin film of water on the surface of the tooth, the efficiency of the laser ablation is enhanced. It has recently been suggested that a more aggressive ablative mechanism, designated as a hydrokinetic effect, occurs when atomized water droplets, introduced between the erbium laser and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…67 Detailed studies of the cutting mechanisms of Er:YAG and Er,Cr:YSGG lasers have revealed that the mechanism by which enamel is removed is basically the same for both laser systems, namely explosive subsurface expansion of interstitially trapped water. 65 The same investigations also failed to show Er,Cr:YSGG laser cutting of a variety of materials which were free of water, which the authors stated was 'contradictory to the existence of the hydrokinetic phenomenon'. 65 An important theoretical extension to the principle of water-based laser ablation of tooth structure is the recently described effect of 'laser abrasion', in which Er:YAG laser energy is used to accelerate the movement of particles of sapphire 30-50 micrometers in diameter in aqueous suspension.…”
Section: Laser Procedures On Dental Hard Tissuesmentioning
confidence: 98%
See 1 more Smart Citation
“…67 Detailed studies of the cutting mechanisms of Er:YAG and Er,Cr:YSGG lasers have revealed that the mechanism by which enamel is removed is basically the same for both laser systems, namely explosive subsurface expansion of interstitially trapped water. 65 The same investigations also failed to show Er,Cr:YSGG laser cutting of a variety of materials which were free of water, which the authors stated was 'contradictory to the existence of the hydrokinetic phenomenon'. 65 An important theoretical extension to the principle of water-based laser ablation of tooth structure is the recently described effect of 'laser abrasion', in which Er:YAG laser energy is used to accelerate the movement of particles of sapphire 30-50 micrometers in diameter in aqueous suspension.…”
Section: Laser Procedures On Dental Hard Tissuesmentioning
confidence: 98%
“…65 The same investigations also failed to show Er,Cr:YSGG laser cutting of a variety of materials which were free of water, which the authors stated was 'contradictory to the existence of the hydrokinetic phenomenon'. 65 An important theoretical extension to the principle of water-based laser ablation of tooth structure is the recently described effect of 'laser abrasion', in which Er:YAG laser energy is used to accelerate the movement of particles of sapphire 30-50 micrometers in diameter in aqueous suspension. As in air abrasion, the impact of these particles causes brittle splitting, resulting in tooth substance removal.…”
Section: Laser Procedures On Dental Hard Tissuesmentioning
confidence: 98%
“…Investigation into this effect has questioned the validity of such claims and in addition, with comparable incident energies, suggested that the ablation rate of the erbium YSGG with enamel is slightly slower than that of erbium YAG. 34 As mentioned above, this might be explained by the absorption dynamics of the YSGG and transfer of conductive heat from …”
Section: Practicementioning
confidence: 93%
“…This laser is similar to the Er:YAG in that it is absorbed by water and both wavelengths ablate through vaporisation of interstitial water, 34 although the absorption coeffi cient is slightly lower (4,000 cm -1 vs 13,000 cm -1 for Er:YAG). When one examines the absorption curve of CHA (enamel), there is a peak, coincident with 2,700 nm, representing absorption by the hydroxyl group (OH -) contained in the mineral molecule ( Fig.…”
Section: Practicementioning
confidence: 98%
“…A water coolant and short pulse duration minimizes the heat transfer to the tooth. [15][16][17] By adjusting the power density, the erbium lasers can be used to create similar microexplosions in soft tissue. This causes a "shaving" or "planing" of the soft tissue rather than the deeper absorbed action of dedicated soft-tissue lasers.…”
Section: Working Of Erbium Lasersmentioning
confidence: 99%